1997
DOI: 10.1016/s1074-7613(00)80525-7
|View full text |Cite
|
Sign up to set email alerts
|

Specific Recognition of Thymic Self-Peptides Induces the Positive Selection of Cytotoxic T Lymphocytes

Abstract: To understand how thymic selection gives rise to T cells that are capable of major histocompatibility complex (MHC)-restricted recognition of antigen but are tolerant of self, we directly examined how peptide/MHC ligands expressed on thymic epithelial cells trigger the positive selection of immature thymocytes. We demonstrate that abundant self-peptides, purified from the H-2D(b) molecules of thymic epithelial cells, are specifically recognized during the positive selection of CD8+ T cells, implying that posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 45 publications
5
67
1
Order By: Relevance
“…Along with charge, the results of Hu et al [3] and Sasada et al [4] suggest that peptide conformation may also be important for interaction with the TCR. One of the self-peptides identified by Hu et al mediated positive selection of the P14 TCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with charge, the results of Hu et al [3] and Sasada et al [4] suggest that peptide conformation may also be important for interaction with the TCR. One of the self-peptides identified by Hu et al mediated positive selection of the P14 TCR.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of these self-peptide complexes has been the focus of several studies. Collectively, these studies provide strong evidence that positive selection can be mediated by ubiquitously expressed self-peptides that contain no significant homology to the cognate peptide of the selected TCR [2][3][4][5][6]. If T cells are indeed selected on ubiquitously expressed self-peptides, then the potential for selfreactivity in the periphery exists.…”
Section: Introductionmentioning
confidence: 94%
“…This consideration might explain why the ND1 selfpeptide was a stronger agonist than variants of cognate peptides that had previously been shown to induce positive selection on the abundant MHC class Ia molecules. In these model systems, positively selecting peptide variants were either scored as very weak agonists/antagonists (19 -21), or were not recognized by mature T cells (16,17). In mice that express a single MHC/peptide complex, peripheral T cells did not react to these highly abundant epitopes, and they expressed TCRs with exceedingly low affinities to these MHC/peptide complexes (27-30, 54, 55).…”
Section: Discussionmentioning
confidence: 99%
“…In the work described here, a single peptide was shown to influence the selection of thymocytes by both a negatively selecting peptide and by unidentified positively selecting ligands. Recent studies have identified several self-peptides that were capable of interacting with and positively selecting TCR transgenic thymocytes (45,46). These experiments suggest that multiple peptides may be involved in the processes of positive and negative selection and that the ability of a given peptide to modulate selection of thymocytes by another peptide may be of physiological importance in thymocyte maturation (47).…”
Section: Discussionmentioning
confidence: 99%